THE USE OF MULTIMEDIA AS AN EFFORT TO IMPROVE ELEMENTARY TEACHER EDUCATION STUDY PROGRAM COLLEGE STUDENTS’ COMPREHENSION ABILITY AND CREATIVE THINKING SKILLS IN FOLLOWING SCIENCE STUDY COURSES - Yudhie Suchyadi; Nurlinda Safitri; Oding Sunardi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
The research objective was to improve the understanding and creative thinking skills of elementary teacher education college student as prospective teachers in following science courses. The research design used is to make college student groups into small groups. During the learning process, observations about college student cooperation during learning with multimedia media were carried out to assess their understanding and creative thinking skills. The results of the observations of each cycle were evaluated as material for reflection in the next cycle to improve college student understanding and creative thinking skills in accordance with predetermined targets. Data analysis was carried out by descriptive quantitative. From the results of the T-test, it was found that there were significant differences. This means that understanding of concepts and Science Process Skills increases after prospective teacher college student experience the science learning process using multimedia learning media. From the results, the average value of understanding the concept increased from 53.61 % to 89.78%.  and science process skills increased the average value from 43.57 to 87.32.  92% of college student gave a positive response, namely agreeing and strongly agreeing that the science lecture process using multimedia learning media can improve science process skills and understanding of material in science subjects for elementary teacher education college student